Thermal gravity-driven convection of near-critical helium in enclosures - Polezhaev, E.B.; Soboleva, V.I. (Физика низких температур, 2003)
The results of numerical simulation of Rayleigh-Benard convection in ³He near the thermodynamic critical point are presented. The mathematical model including the full Navier-Stokes equations with two-scale splitting of the pressure and the van der Waals equation of state is applied. The known experimental data on ³He are used in simulations. On the basis of the calibration laws the "real" Rayleigh and Prandtl numbers are estimated. It is shown that one should agree these "real" criteria of similarity in the model and physical media to approach results of simulations to experiments. The Rayleigh number characterising the convection onset is defined from obtained numerical data. This number is shown to be in a good agreement with known experimental and theoretical values.